A revised ammonoid biostratigraphy for the Aptian of NW Africa: Essaouira-Agadir Basin, Morocco. (November 2017) - Luber, Tim L.; Bulot, Luc G.; Redfern, Jonathan; Frau, Camille; Arantegui, Angel; Masrour, Moussa
Abstract: A revised ammonoid biostratigraphy is presented for the Aptian of NW Africa, Essaouira-Agadir Basin (EAB ), Morocco, based on detailed analysis of 5 key sections. A number of bio-events are documented and 26 genus and 43 species fully documented, forming the largest published Aptian ammonite collection made from NW Africa. The section at Tiskatine is documented as the type section, and 8 zones and subzones are defined, of which 5 are new. This work allows correlation of the Aptian of theEAB to the Standard Mediterranean Ammonite Scale (SMAS ). Two main hiatuses are identified at the scale of the basin scale: a major one that includes most of the lower Aptian and the base of the upper Aptian and a second one encompass the top of the upper Aptian and the base of the lower Albian. The ammonite fauna displays a clear Tethyan palaeobiogeographic character affected by a fairly high degree of endemism at the genus and species level. The new genus and species Elsaisabellia tiskatinensis is introduced.